2017
DOI: 10.1590/1984-70332017v17n2c26
|View full text |Cite
|
Sign up to set email alerts
|

IPR 100 - Rustic dwarf Arabica coffee cultivar with resistance to nematodes Meloidogyne paranaensis and M. incognita

Abstract: 'IPR 100' was derived from a crossing between "Catuaí" and a hybrid . 'IPR 100' is a medium size dwarf cultivar with high rusticity, with late ripening cycle, and with resistance to Meloidogyne paranaensis and to some M. incognita populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
0
19
1
Order By: Relevance
“…In this study, the genotypes MG 0179‐1 and MG 0179‐3 had RFs < 1, confirming their resistance to M. paranaensis as presented by Salgado et al (2014) and Peres et al (2017). On the other hand, cultivar IPR 100, which had an RF < 1 in other studies (Andreazi et al, 2015; Sera et al, 2017), had an RF slightly greater than 1 in this study. This difference in the value of the RF may be related to the physiological differences in the nematode aggressiveness.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In this study, the genotypes MG 0179‐1 and MG 0179‐3 had RFs < 1, confirming their resistance to M. paranaensis as presented by Salgado et al (2014) and Peres et al (2017). On the other hand, cultivar IPR 100, which had an RF < 1 in other studies (Andreazi et al, 2015; Sera et al, 2017), had an RF slightly greater than 1 in this study. This difference in the value of the RF may be related to the physiological differences in the nematode aggressiveness.…”
Section: Discussioncontrasting
confidence: 52%
“…The relatively high root surface area and volume of the Catuaí IAC 62 and IPR 100 cultivars resulted from the intensive selection of breeding programmes and make them successful cultivars for growers compared with progenies that have yet to enter the market. Sera et al (2017) and Martins, Pedroso, Fazuoli, and Gonçalves (1992) demonstrated the high potential for the production of Catuaí 62 and IPR 100, highlighting them among other cultivars in the field. Nevertheless, when a field is infested by M. paranaensis, the yield potential of Catuaí 62, indicated by the robust root system, is decreased due to a reduction in the root surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for IPR 100 (Sera et al, 2017) and IPR 106 (Ito el al., 2008), most Coffea arabica L. cultivars are highly susceptible to M. paranaensis. Genetic resistance is the most effective method to cultivate coffee in infested soils (Bertrand and Anthony, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…IPR 100 is the only one cultivar that has been widely grown in infested areas in Brazil and presents resistance level to M. paranaensis similar to rootstock C. canephora cv. Apoatã IAC 2258 (Andreazi et al, 2015a;Sera et al, 2017). In the coffee breeding program of IAPAR, Arabica coffee cultivars resistant to nematodes have been developed using 'IPR 100' as resistance source, which is resistant to M. paranaensis.…”
Section: Introductionmentioning
confidence: 99%